THE IMPACT OF THE NEW WORLD ECONOMIC ORDER ON THAILAND AND ITS STRATEGIC MEASURES - Worabhuri Moolsin; Pon Puttanukorn; Phawat Rujachan; Ananya Inphum (Proceedings on Engineering Sciences)
Following the conclusion of World War II on September 2, 1945, the global community transitioned into a period characterized by both peace and accelerated progress. The advancements in the fields of finance, education, science, and medicine, particularly in Western societies, were predominantly spearheaded by the Anglo-Saxon nations, with the United States taking a prominent role. Then, the Anglo-Saxons, under the leadership of the United States, and the impact of the Anglo Saxons on business and the economy is a subject of considerable interest. In the present year of 2023, we are observing a significant shift in the Western nations that were formerly regarded as the dominant global powers. These nations, commonly referred to as the "Developed nations," including the G7, have experienced a substantial decline in their economic influence. Specifically, their collective economic share, which once accounted for 70 percent, has diminished to 30.7 percent over the course of the past three decades. In the year 2021, the emerging economies of the BRICS group have surpassed the overall market share. In light of the significant population percentages of 31.5 percent and 41 percent within the G7 group in 2022, it is pertinent to consider their ability to effectively respond to and capitalize on the emerging "new world order" of the 21st century. Given this context, a pertinent question arises: should Thailand persist in adhering to the Western world order? This essay aims to analyze the forthcoming developments and to examine the economic policies implemented by the G7 and BRICS groups, with a specific focus on their impact on the global economy as well as the economy of Thailand.